Inactivation of liver S-adenosylhomocysteine hydrolase in vitro of rats treated with erythro-9-(2-hydroxynon-3-yl)adenine. - Kajander, E O (1982)
S-Adenosylhomocysteine hydrolase activity decreased in vitro time-dependently in liver homogenates obtained from rats treated in vivo with erythro-9-(2-hydroxynon-3-yl)adenine, a potent inhibitor of adenosine deaminase. The inhibitor in itself had no effect on the stability of the hydrolase. The inactivation of S-adenosylhomocysteine hydrolase was irreversible, proceeded fairly rapidly at a low temperature (0 degrees C) and showed first-order reaction kinetics. Adenosine was found to accumulate in these tissue homogenates during storage. Several lines of evidence suggest that adenosine caused the observed suicide-like inactivation post mortem. Pre-incubation of purified S-adenosylhomocysteine hydrolase at 0 degrees C with adenosine showed a half-maximal inactivation rate at 33 microM substrate concentration; the rate constant of inactivation was 0.01 min-1. Inactivation during tissue preparation and storage complicates the assay of S-adenosylhomocysteine hydrolase activity in samples that contain an inhibitor of adenosine deaminase. These results also suggest that the decrease of S-adenosylhomocysteine hydrolase activity reported to occur in several disturbances of purine metabolism should be re-examined to exclude the possibility of inactivation of the enzyme in vitro.